Mefenamic Acid Selective Membranes Sensor and Its Application to pharmaceutical Analysis (Baghdad Science Journal, 2025)
PVC membrane sensor for the selective determination of Mefenamic acid (MFA) was constructed. The sensor is based on ion association of MFA with Dodecaphospho molybdic acid (PMA) and Dodeca–Tungstophosphoric acid(PTA) as ion pairs. Nitro benzene (NB) and di-butyl phthalate (DBPH) were used as plasticizing agents in PVC matrix membranes. The specification of sensor based on PMA showed a linear response of a concentration range 1.0 × 10–2 –1.0 × 10–5 M, Nernstian slopes of 17.1-18.86 mV/ decade, detection limit of 7 × 10-5 -9.5 × 10 -7M, pH range 3 – 8 , with correlation coefficients lying between 0.9992 and 0.9976, respectively. By using the ionphore based on PTA gives a concentration range of 1.0 × 10–4 –1.0 × 10–5 M, Nernstian slope of 17.18-18.4 mV/ decade, limit of detection 8.0 × 10–6-9.3 × 10-5M,pH range 3 – 8 and correlation coefficients range between 0.9984 and 0.9891, respectively. The measurement interferences in the presence of Li+, Na+, Mg2+ Ca2+, Fe3+and Al3+ were studied using separate and match potential methods for selectivity coefficient determination. The method was applied for the determination of Mefenamic Acid in pharmaceutical preparations